Rational design of chemical ligands for selective mitochondrial targeting - Rimpelová, Silvie; Bříza, Tomáš; Králová, Jarmila; Záruba, Kamil; Kejík, Zdeněk; Císařová, Ivana; Martásek, Pavel; Ruml, Tomáš; Král, Vladimír (Bioconjugate chemistry, 2013)
The rational design of molecules with selective intracellular targeting is a great challenge for contemporary chemistry and life sciences. Here, we demonstrate a rational approach to development of compartment-specific fluorescent dyes from the γ-aryl substituted pentamethine family. These novel dyes exhibit an extraordinary affinity and selectivity for cardiolipin in inner mitochondrial membrane and possess excellent photostability, fluorescent properties, and low phototoxicity. Selective imaging of live and fixed mitochondria was achieved in various cell lines using nanomolar concentrations of these dyes. Their high localization specificity and low toxicity enables study of morphological changes, structural complexity, and dynamics of mitochondria playing a pivotal role in many pathological diseases. These far-red emitting dyes could also serve in a variety of biomedical applications.
Keywords: kultivované buňky; buněčné linie; Cardiolipins; myši; Cells, Cultured; kur domácí; nádorové buněčné linie; Cell Line, Tumor; lidé; Humans; Chickens; Mice; Animals; molekulární modely; Crystallography, X-Ray; zvířata; DNA; fluorescenční barviva; ligandy; mitochondrie; kardiolipiny; Mitochondria; Fluorescent Dyes; Cell Line; Ligands; Models, Molecular; krystalografie rentgenová